HUBUNGAN BEBAN KERJA DENGAN KELELAHAN MATA PADA TEKNISI HANDPHONE DI PLAZA MILLENIUM TAHUN 2015 - tommy pikarokaro; eka lestari mahyuni; halinda sari lubis (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Many Cellular phone technicians used eyes organ in repairing cellular phone, and caused eyes fatigue like : poignant eyes, aqueous eyes, clouded vision, and neck pain. Besides that, cellular phone technicians also needed detail in using every components on cellular phone because they were very tiny. This research used analysis survey with cross sectional design. Population are 67 cellular phone technicians and sample are 33 cellular phone technicians which were decided by purposive sampling which one of the criteria is willing to be respondent. Method of collecting data used Photostress recovery Test and questionnaire Visual Fatigue Index. Work load could be seen from average number of phone repaired in 11 hours working per a day. The result of research showed that a number of workers whose got eyes fatigue based on questionnaire are 18 people (54,5%), got right eyes fatigue based on Photostress Recovery Test are 20 people (60,6%) and got left eyes fatigue based on photostress recovery Test are 17 people (51,5%), a number or workers did burden work over average are 17 people (51,5%). The result of analyzing test, it is significant relation between work load per days and eyes fatigue based on questionnaire (p=0,003), work load per days and right eyes fatigue category (p=0,023), work load per days and left eyes fatigue (p=0,009) based on photostress recovery test